Elucidation of the potential disease-promoting influence of IgM apoptotic cell-reactive antibodies in lupus. (June 2016) - Malik, M; Arora, P; Sachdeva, R; Sharma, L; Ramachandran, V G; Pal, R
The undigested remnants of apoptosis are believed to stimulate the generation of autoantibodies in lupus. The biological properties of initiator, disease-specific IgM antibodies that specifically recognize apoptotic cells, readily detected in the sera of lupus patients, remain unclear. Apoptotic cell-reactive IgM monoclonal antibodies (generated from lupus-prone mice), as opposed to control IgM, preferentially stimulated maturation of bone marrow-derived dendritic cells (BMDCs) derived from such mice, relative to BMDCs derived from healthy mice. An influence of both antibody specificity and cell genotype was also apparent in the secretion of signature inflammatory cytokines. Immunization of such antibodies in lupus-prone animals induced increases in total serum IgG levels, with the elicited antibodies also preferentially recognizing moieties on dying cells. An expanded specificity was apparent both upon Western blot on cellular lysate and from the enhanced recognition of dsDNA, Ro60, RNP68 and Sm; the antibody most efficient in mediating autoreactive diversity, while being germline encoded, also induced the highest degree of phenotypic changes on BMDCs. Apoptotic cell-reactive IgM antibodies may therefore be potentially capable of influencing the course of systemic autoimmune disease by affecting both innate and adaptive immunity.